Government hospital nurses’ perspectives on patient safety culture - Tan, Geok Eng; Ooi, Cheow Peng; Soh, Kim Lam (Universiti Putra Malaysia Press, 2025)
Introduction: A patient safety culture is essential for healthcare providers to deliver safe, quality patient care. Inadequate levels of patient safety culture are linked to many significant medical errors in hospital settings. This study will determine nurses’ perceptions of patient safety culture in a government hospital. Method: A survey using the Hospital Survey on Patient Safety Culture to asses nurses’ patient safety culture perception in a government hospital. Results: The total mean score for patient safety culture was 46.67SD±14.21. The highest score was “Organisational learning—continuous improvement,” and the lowest was “Non-punitive response to errors,” with 78.4% and 11.6%, respectively. Conclusion: The average patient safety culture score was below 50%, which is lower than in other countries. The lowest score in the “Non-punitive response to errors” indicates that hospital management needed to overhaul the error reporting system to foster an efficient, blame-free, and professional environment, thereby reducing nurses’ fear of reporting errors.